(untitled) (Applied Biological Research, 2014)
Four different stocks of grass carp from different geographical locations viz., Kolkata, Kaikaluru, BRP and Thanjavur representing varied environmental conditions were collected from Kolkata (West Bengal), Kaikaluru (Andhra Pradesh), Shimoga (Karnataka) and Thanjavur (Tamilnadu). The stocks were marked using fin cauterization for easy identification during the growth behaviour studies. Growth behavior sudies conducted under same environmental and management conditions. RAPD analysis was performed for different stocks of grass carp. Of the 100 decamer primers screened, seven primers (OPA 1, OPA 18, OPB 11, OPB 19, OPD 11, OPD 18 and OPE 10) gave consistent and at least two polymorphic bands. The RAPD analysis showed that Kolkata stock had 2.74 to 14.72% higher polymorphic bands in comparison with other stocks. The Kolkata stock was found closely related to Kaikaluru stock but distantly related to Thanjavur stock. Growth trials indicated better performance of Kolkata stock in comparison to other stocks. The r2value between the % polymorphism and mean body weight attained by different stocks of grass carp showed that these two parameters were positively correlated.